Measuring welfare, inequality and poverty with ordinal variables - Jacques Silber; Gaston Yalonetzky (Global Labor Organization (GLO), 2021)
The key challenge in making distributional comparisons with ordinal data is the lack of commensurability of the distances between the ordered categories. This chapter provides a critical review of the most recent theoretical developments addressing this challenge and providing methods for ethical poverty, welfare, and inequality comparisons with univariate ordered multinomial distributions.
Keywords: D31; D63; I31; I32; 330; inequality; ordinal variables; partial ordering; poverty; welfare